2010
DOI: 10.1128/jvi.01940-09
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of AKT and MAP Kinase Dictates Virus-Host Cell Fusion

Abstract: Viruses of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 61 publications
(78 reference statements)
4
20
0
Order By: Relevance
“…2B). These analyses showed significant overrepresentation of phosphoproteins involved in MAPK pathways, ERK/MAPK, p38, and JNK signaling, which all are known to be activated during SeV infection . Our data also indicates that Rho family of GTPases and HIPPO signaling was activated during infection.…”
Section: Resultssupporting
confidence: 65%
“…2B). These analyses showed significant overrepresentation of phosphoproteins involved in MAPK pathways, ERK/MAPK, p38, and JNK signaling, which all are known to be activated during SeV infection . Our data also indicates that Rho family of GTPases and HIPPO signaling was activated during infection.…”
Section: Resultssupporting
confidence: 65%
“…Additionally, it was demonstrated that activation of ERK1/2 is required for viral entry using Sendai virus-like particles as a model for Paramyxovirus infection [48]. In this study, ERK1 was identified in RSV infected cells only, and ERK2 was detected with higher abundance in infected cells.…”
Section: Discussionmentioning
confidence: 61%
“…Subsequently, DC-SIGN engagement can initiate both MAPK and phosphatidylinositol 3-kinase (PI3K)/ mTOR signaling with phosphorylation of ERK1/2 and Akt (5,7,38,48). ERK1/2 signaling is involved in infection, replication, and host responses to a number of pathogens (19), particularly viruses (41,48,49,61). PI3K and mTOR have well-defined roles in controlling activation of adaptive immune responses but have now also been shown to be critical in regulation of innate immunity (58).…”
Section: Discussionmentioning
confidence: 99%
“…Ligand binding to or antibody crosslinking of DC/L-SIGN has been shown to result in phosphorylation of multiple cellular kinase pathways, including ERK1/2, p38/ mitogen-activated protein kinase (MAPK), Akt, and c-Raf (5,7,38,48). Similarly, RSV phosphorylates ERK1/2 during infection of epithelial cells (49). As moderate changes were observed in DC maturation and cytokine and chemokine production following DC/L-SIGN neutralization and RSV exposure, we examined the impact of RSV G on signaling events in 3T3 parent cells and 3T3-DC-SIGN and 3T3-L-SIGN transfectants.…”
Section: Neutralization Of Dc/l-sign Does Not Reduce Rsv Infection Ofmentioning
confidence: 99%